Validating Systemic Factors of STEM Integration in Early Childhood Education and Care Using Mixed Methods - Kok Ming Goh; Anuthra Sirisena (SEA-CECCEP, 2025)
The rapid global push toward STEM education and the increasing accessibility of robotics have prompted renewed attention to their integration in Early Childhood Education and Care (ECEC). While robotics in early learning has been shown to foster creativity, problem-solving, and socio-cognitive development, its adoption in Southeast Asia remains fragmented, hindered by uneven infrastructure, limited teacher readiness, and inconsistent curriculum alignment. This study aims to map the systemic factors shaping robotics integration in ECEC and to provide a strategic framework for policy and practice across the region. Employing a mixed-methods research design with 17 experts, including early childhood educators, curriculum specialists, and policymakers, the research combined the Nominal Group Technique (NGT) to identify and prioritize key factors, Interpretive Structural Modeling (ISM) to explore hierarchical interdependencies, and the Fuzzy Delphi Method (FDM) to validate expert consensus. Findings revealed five critical factors: teacher competency in STEM pedagogy, availability of age-appropriate robotics, curriculum integration, cost and infrastructure, and parental support and digital literacy. ISM analysis highlighted a dependency chain in which parental support and infrastructure form the foundational conditions, robotics availability and teacher competency act as drivers, and curriculum integration stands as the dependent, strategic goal. FDM validation confirmed strong consensus on teacher competency and curriculum reform, moderate consensus on infrastructure and robotics availability, and conditional consensus on parental engagement, with refinements emphasizing culturally relevant tools, innovative financing, and community-based digital literacy. The study concludes that sustainable integration requires a sequenced, systemic approach addressing foundational and enabling factors before curricular reform. These insights provide a roadmap for educational stakeholders to guide equitable and context-sensitive STEM transformation in early childhood education.